BUSINESS ETHICHS OF MUSLIM TRADERS FROM AN ISLAMIC PERSPECTIVE AND ITS IMPACT ON THE WELFARE OF MUSLIM TRADERS IN THE TRADITIONAL MARKET OF MOTONG, UTAN SUB-DISTRICT, SUMBAWA DISTRICT - SAFITRI, RIZA ANGGRAINI; Huzaini, Moh.; Jufri, Akhad (Laboratorium Riset Ekonomi, 2025)
This study aims to determine the types of goods traded by traders and analyze the business ethics of traders and analyze the level of welfare of Muslim traders in Motong Market, Utan District, Sumbawa Regency. This research uses a descriptive qualitative approach. The type of research used is field research. Data collection techniques used are interviews, observation, and documentation. Determination of informants using purposive and snow ball. The conclusions of this study are: There are five groups of goods traded, namely agricultural products, home industry, fishery products, basic necessities and various types of snacks; Most traders have applied Islamic business ethics, such as being tauhid, honest, and transparent, not using false oaths, being lenient and generous, building good relationships and setting prices transparently. Two did not apply Islamic business ethics, such as being dishonest in selling, selling goods that are not of good quality; Most traders have obtained good welfare (hayaatan tayyibah) and have been qana'ah. Despite living in simplicity, they are already included in a prosperous family, because they have been able to fulfill their dharuriyat and hajiyat needs. Only one person has not because he has not been able to fulfill the needs of Hifdzu Diin, namely neglecting to perform the five daily prayers. Keywords: Islamic Business Ethics, Traders, Islamic Welfare This study aims to determine the types of goods traded by traders and analyze the business ethics of traders and analyze the level of welfare of Muslim traders in Motong Market, Utan District, Sumbawa Regency. This research uses a descriptive qualitative approach. The type of research used is field research. Data collection techniques used are interviews, observation, and documentation. Determination of informants using purposive and snow ball. The conclusions of this study are: There are five groups of goods traded, namely agricultural products, home industry, fishery products, basic necessities and various types of snacks; Most traders have applied Islamic business ethics, such as being tauhid, honest, and transparent, not using false oaths, being lenient and generous, building good relationships and setting prices transparently. Two did not apply Islamic business ethics, such as being dishonest in selling, selling goods that are not of good quality; Most traders have obtained good welfare (hayaatan tayyibah) and have been qana'ah. Despite living in simplicity, they are already included in a prosperous family, because they have been able to fulfill their dharuriyat and hajiyat needs. Only one person has not because he has not been able to fulfill the needs of Hifdzu Diin, namely neglecting to perform the five daily prayers.Keywords: Islamic Business Ethics, Traders, Islamic Welfare